DYNAMICS OF CHANGE IN UNITED STATES POLICY IN THE SYRIAN CRISIS: ANALYSIS OF THE TRANSITION FROM DIPLOMACY TO INTERVENTION - Fauzi, Wajid; Rochani Adi, Ida; Hindun, Hindun (Rubikon : Journal of Transnational American Studies, 2025)
The United States' policy toward the Syrian crisis (2011-2019) was marked by a significant and often inconsistent transition from diplomatic caution to direct military intervention. This article analyzes the dynamics of this policy evolution, moving beyond traditional state-centric explanations to examine the influence of cross-border flows. It argues that the transition was not a linear progression but a reactive and fragmented process driven by the interplay of three key factors: the failure of established international diplomatic mechanisms to resolve the conflict; the transnationalization of the threat landscape with the rise of the Islamic State (ISIS); and the powerful, albeit fluctuating, influence of global media narratives depicting humanitarian atrocities. This study maps the critical junctures that compelled policy recalibration by employing a qualitative process-tracing methodology and discourse analysis of official documents, presidential statements, and media reports. The findings demonstrate that key decisions from the "red line" ultimatum to the initiation of Operation Inherent Resolve were profoundly shaped by forces that transcended national borders, forcing policymakers to react to non-state actors, global information flows, and normative pressures. The research embodies an analytical and process-oriented approach that systematically investigates the evolution of US foreign policy during the Syrian crisis, emphasizing the underlying dynamics that prompted the transition from diplomatic engagement to direct intervention.